'Far reaching and perhaps destructive'? The 1974–79 Labour Government, devolution and the emergence, and failure, of the Scotland and Wales Bill. (2nd January 2021) - Evans, Adam
ABSTRACT: The story of devolution in the United Kingdom is a long and chequered one which long predates the establishment of devolved legislatures in Scotland and Wales after referendums in 1997. The devolution programme of Tony Blair's Labour Government came eighteen years after the failure of the 1974–79 Labour Government's attempts at establishing Scottish and Welsh devolution. This article explores how after establishing a Royal Commission on the Constitution in his first Government, Wilson would be left to take up the reins of devolution again after the two elections of 1974. It focuses on how Harold Wilson, and then James Callaghan, developed, often with huge reluctance and great caution, devolution proposals that would eventually form the Scotland and Wales Bill (the Labour Government's first set of legislative proposals for devolution). The bill endured a tortuous fate in parliament and its slow progress eventually ground to a final halt in February 1977. However, despite the bill's failure, the work that went into developing it and the concessions that were made by the government during its aborted journey through the House of Commons had consequences that were felt during the remainder of the 1974–79 Labour Government's fraught existence and long after.